Papaya ringspot virus–Carica papaya pathosystem - Cabrera Mederos, Dariel (2020)
This chapter explains why papaya ringspot virus (PRSV) is a global threat to Carica papaya L. and discuses some aspects papaya origin, taxonomy, distribution, global production, and genetic and genomic resources. PRSV belongs to the genus Potyvirus, family Potyviridae, and may cause mosaicism, leaf deformation, and concentric rings in fruits. Two PRSV biotypes have been identified, P and W. Hosts include Chenopodium quinoa, Cucumis melo, Cucumis sativus, Cucurbita maxima, Cucurbita moschata, Cucurbita pepo, Diplocyclos palmatus, Momordica charantia, Robinia pseudoacacia, and Clitoria ternatea. PRSV may be transmitted by seeds and by aphids in a nonpersistent manner. Detection methods include indicator plants and serological and molecular methods. PRSV integrated management may be implemented by plantation season, raising border crop, cultivar preference, virus-free seedlings, application of insecticides, regular weeding, and eradication of infected plants. Here, we summarize the main aspects of PRSV, which is the most damaging virus pathogen to papaya worldwide.